Evaluasi sistem pembelajaran online dimasa pandemi covid-19 - Abidin Wakano; Eko Wahyunanto Prihono; Nur Hasanah; Fitria Lapele (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This research aims to determine the feasibility of the online learning system CIPP evaluation instrument and to evaluate the online learning system during the Covid-19 pandemic at IAIN Ambon. It was an evaluation research, using the CIPP (Context, Input, Process, Product) model. The research subjects were students at the Faculty of Education and Teacher Training at IAIN Ambon. Moreover, the data collection was carried out using a questionnaire instrument. Instrument validity used expert judgment. The reliability of the instrument was analyzed using Alpha Cronbach. The result analysis used quantitative descriptive method. The results showed that: 1) the instrument was feasible and suitable used as a measuring tool for the evaluation of the online learning system at IAIN Ambon based on validity and reliability tests. 2) the results of the evaluation in terms of context showed that the average achievement was 95% in the very good category. The evaluation from the input aspect showed that the average achievement was 91% in the very good category. While the evaluation in terms of the process aspect showed that the average achievement was 93% in the very good category and the evaluation from the product aspect showed that the average achievement of 79% was in the good category.Penelitian ini bertujuan untuk mengetahui kelayakan instrumen evaluasi CIPP sistem pembelajaran online dan melakukan evaluasi sistem pembelajaran online selama pandemi Covid-19 di IAIN Ambon. Penelitian ini merupakan penelitian evaluasi, menggunakan model CIPP (Context, Input, Process, Product). Subyek penelitian adalah mahasiswa di Fakultas Ilmu Tarbiyah dan Keguruan di IAIN Ambon. Pengumpulan data dilakukan menggunakan instrumen kuesioner. Validitas istrumen menggunakan expert judgement. Reliabilitas instrumen dianalisis menggunakan Alpha Cronbach. Analisis hasil menggunakan metode deskriptif kuantitatif. Hasil penelitian menunjukkan: 1) instrumen layak dan sudah sesuai untuk digunakan sebagai alat ukur evaluasi sistem pembelajaran online di IAIN Ambon berdasarkan uji validitas dan reliabilitas. 2) hasil evaluasi ditinjau dari aspek konteks menunjukkan pencapaian rerata sebesar 95% dalam kategori sangat baik. Adapun evaluasi dari aspek input menunjukkan pencapaian rerata sebesar 91% dalam kategori sangat baik. Sedangkan evaluasi ditinjau dari aspek proses menunjukkan pencapaian rerata sebesar 93% dalam kategorisangat baik dan evaluasi dari aspek produk menunjukkan pencapaian rerata sebesar 79% tergolong dalam kategori baik.